Late Wittgenstein’s money - L. Eden Steininger (Finance and Society)
This essay examines the contemporary discourse on inflation through the lens of Wittgenstein’s late work on language games. Using his concept of hinge propositions – beliefs upon which language games depend – I offer a novel perspective on the public good that is price stability. In particular, I first consider the inflation hypothesis as a derivative of the commodity theory of money and therefore inherently linked to a purely quantitative regime of monetary management. I then argue that, based on the hinge proposition that money is a creature of law, money’s value might instead be grasped and engaged on the basis of its political and qualitative dimensions.